Microscale Architecture in Biomaterial Scaffolds for Spatial Control of Neural Cell Behavior - Meco, Edi; Lampe, Kyle J. (Frontiers in Materials, 2018)
Biomaterial scaffolds mimic aspects of the native central nervous system (CNS) extracellular matrix (ECM) and have been extensively utilized to influence neural cell (NC) behavior in in vitro and in vivo settings. These biomimetic scaffolds support NC cultures, can direct the differentiation of NCs, and have recapitulated some native NC behavior in an in vitro setting. However, NC transplant therapies and treatments used in animal models of CNS disease and injury have not fully restored functionality. The observed lack of functional recovery occurs despite improvements in transplanted NC viability when incorporating biomaterial scaffolds and the potential of NC to replace damaged native cells. The behavior of NCs within biomaterial scaffolds must be directed in order to improve the efficacy of transplant therapies and treatments. Biomaterial scaffold topography and imbedded bioactive cues, designed at the microscale level, can alter NC phenotype, direct migration, and differentiation. Microscale patterning in biomaterial scaffolds for spatial control of NC behavior has enhanced the capabilities of in vitro models to capture properties of the native CNS tissue ECM. Patterning techniques such as lithography, electrospinning and 3D bioprinting can be employed to design the microscale architecture of biomaterial scaffolds. Here, the progress and challenges of the prevalent biomaterial patterning techniques of lithography, electrospinning, and 3D bioprinting are reported. This review analyzes NC behavioral response to specific microscale topographical patterns and spatially organized bioactive cues.